Forestry, illegibility and illegality in Omkoi, Northwest Thailand - Bobby Anderson; Patamawadee Jongruck (Forest and Society, 2017)
Opium poppy cultivation in Thailand fell from 12,112 hectares in 1961 to 281 ha in 2015. One outlier exists: Chiang Mai province’s remote southwestern district, Omkoi. 90% of the district is a national forest reserve where human habitation is illegal. However, an ethnic Karen population has lived there since long before the law that outlawed them was created, unconnected to the state by road, with limited or no access to health, education and other services: they cultivate the majority of Thailand’s known opium poppy, because they have little other choice. They increasingly rely on cash-based markets, their lack of citizenship precludes them from land tenure which might incentivize them to grow alternate crops, and their statelessness precludes them from services and protections. Nor is the Thai state the singular Leviathan that states are often assumed to be; it is a collection of networks with divergent interests, of whom one of the most powerful, the Royal Forestry Department, has purposely made Omkoi’s population illegible to the state, and has consistently blocked the attempts of other state actors to complexify this state space beyond the simplicity of its forest. These factors make short-term, high-yield, high value, imperishable opium the most logical economic choice for poor Karen farmers residing in this “non-state” space.